Zinc Therapy in Dermatology: A Review - Mrinal Gupta; Vikram K. Mahajan; Karaninder S. Mehta; Pushpinder S. Chauhan (Dermatology Research and Practice)
Zinc, both in elemental or in its salt forms, has been used as a therapeutic modality for centuries. Topical preparations like zinc oxide, calamine, or zinc pyrithione have been in use as photoprotecting, soothing agents or as active ingredient of antidandruff shampoos. Its use has expanded manifold over the years for a number of dermatological conditions including infections (leishmaniasis, warts), inflammatory dermatoses (acne vulgaris, rosacea), pigmentary disorders (melasma), and neoplasias (basal cell carcinoma). Although the role of oral zinc is well-established in human zinc deficiency syndromes including acrodermatitis enteropathica, it is only in recent years that importance of zinc as a micronutrient essential for infant growth and development has been recognized. The paper reviews various dermatological uses of zinc.